Use of p48 flow diverters with hydrophilic polymer coating under prasugrel single antiplatelet therapy for intracranial aneurysms arising from small-caliber vessels (≤ 2 mm): case series, complication, and occlusion rates - Khanafer, Ali; Palmarola, Pablo Albiña; Hajiyev, Kamran; von Gottberg, Philip; Filioglo, Andrei; Forsting, Michael; Henkes, Hans (Frontiers in Neurology, 2025)
PurposeFlow-diverter (FD) stents have become an established treatment for intracranial aneurysms in recent years, but their use for aneurysms in distal cerebral vessels with small caliber remains controversial. This study reports our single-center experience in using hydrophilic polymer-coated (HPC) p48 MW FDs with prasugrel single antiplatelet therapy (SAPT) to treat ruptured and unruptured aneurysms arising from small-caliber vessels (≤ 2 mm).MethodsA prospectively maintained database was retrospectively reviewed to identify all cases of intracranial aneurysms arising from small-caliber vessels (≤ 2 mm) treated with the p48 MW HPC device under SAPT (Prasugrel). The clinical presentation and outcomes, periprocedural and postprocedural complications, and degree of occlusion at follow-up (FU) were evaluated.ResultsA total of 62 patients (70.7% women) with 65 aneurysms were treated. Two patients (3.2%) experienced complications associated with FD use. No cases of aneurysm rupture or hemorrhagic complications associated with antiplatelet therapy or FD treatment were recorded. The rate of complete occlusion was 71.9% in the early FU period (3–6 months) and 86.1% in the initial 12-month period.Conclusionp48 MW HPC FDs with prasugrel SAPT showed high safety in the treatment of ruptured and unruptured aneurysms arising from small-caliber vessels (≤ 2 mm), and high occlusion rates at early- and mid-term FU.